Evaluation of Bandeng Cluster Program to Empower Economy in Semarang - Mardika, Riski Era; Dwimawanti, Ida Hayu; Rihandoyo, Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2012)
Bandeng Cluster Program in Semarang is one of the innovative idea to empower economy. It is a response for empowering issue that lower economical class must be empowered so they can fulfill their needs. This program is to optimalize economical local resources in Semarang which is bandeng The target is all UKM bandeng in Semarang.The goal of this research is to evaluate Bandeng Cluster implementation. This evaluation to make known the success rate, resist factor, and future recomendation by analyse the program using these indicator: input, proccess, output, outcome, benefit and impact. This research use Snowball Sampling technique and the methods of data collection is use indept interview with purposive system to choose the informants. The result of the research show that Bandeng Cluster program its not effective. The result from Program Evaluation Form (EK-1) and (EK-2) showed that value of each activity in Bandeng Cluster program worked ineffectively. Its because of implementation of Statute and Bylaws was not implemented to the fullest also no punishment if there is violation.. Unhealthy competition between UKM also affected because this program yet reach smaller UKM who needs help. Mechanism to use facility also can not be done because of its location is too far, the different kind of bandeng product, and the different taste product of each UKM. Resistant factors from the Bandeng Cluster program are the concept; the characteristic of the cluster is not ideal; hard access to find the main ingredient; unrealized capital access; inactive cluster workers; low coordination; bureaucracy; unequal aid; and also lack of concern and control of government.